The Epistemology of Ijtihad Irsyadi in Fatwas: A Deconstruction of Takhrij Mażhabi through Case Studies of the Lirboyo Fatwa Council - Muhammad Ibtihajuddin; Abdul Fattaah; Moch. Nurcholis; Zakka Asvi Auful Shohi Muhammad (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2025)
The rigidity of the takhrīj mażhabi methodology in pesantren fatwa traditions necessitates a new epistemological approach that is more responsive to contemporary realities. This study aims to explore ijtihād irsyādi as a methodological alternative that maintains continuity with classical tradition while enabling contextual creativity grounded in maqāṣid al-sharī’ah. Employing a qualitative-descriptive-analytical-exploratory approach and a case study method focused on the fatwas of the Lajnah Bahtsul Masail (LBM) Lirboyo from 2019 to 2024, the analysis reveals significant epistemological transformation in istinbath structures. Key findings demonstrate that ijtihād irsyadī prioritizes maslahat (public interest), referential flexibility, and social interpretation as legal foundations, replacing the deductive-formalistic patterns of madhhab-based takhrīj. This approach reinterprets classical authority through maqāṣid frameworks without negating its legitimacy, as evidenced in the 2023 BPJS Healthcare fatwa that teleologically reconstructs social insurance concepts via taḥrīr al-mafhūm (conceptual liberation), tanqīḥ al-manāṭ (ratio legis purification), and ta'līl maqāṣidī (teleological justification). The novelty lies in articulating an adaptive, integrative fatwa epistemology that proactively engages temporal dynamics, offering a reformative paradigm for Indonesian pesantren fatwa methodologies and a substantive contribution to renewing contemporary Islamic legal thought.